The Making of Power Shortage: The Sociotechnical Imaginary of Nationalist High Modernism and Its Pragmatic Rationality in Electricity Planning in Taiwan. Issue 3 (1st September 2018) - Yang, Chih-yuan; Szerszynski, Bronislaw; Wynne, Brian
Abstract: High modernism, the dominant sociotechnical imagination in postwar Taiwan, manifested in tacit answers to the questions of what a better society would look like and the most pragmatic and viable approach to make the particular dreamed-of future become reality. This article explores the exclusion of alternative energy futures brought about by a high modernist imaginary. This imaginary underlies a strategy of emphasizing shortage at present and prosperity in the future—as long as the current shortage is solved in a reliable way. Focusing on the contention over energy supply between 2011 and 2015, this article provides an analysis of how power shortages are presented in discursive ambiguity, how the claimed crisis over the electricity shortage moves to the center of public debate via the institutional practices of power rationing, and how its public authority is established through collective witness. Renewable energy is continually represented as an "immature" and "unviable" technology when it comes to satisfying the nation's need, through particular routinized practices in the calculation of "reserve margins" in electricity planning and the collective witnessing of (limited) operating reserves. We argue that both of these come with their own assumptions and political implications and therefore invite scrutiny.